New insights into semen separation techniques in buffaloes - Andrei, Crina Raluca; Posastiuc, Florin Petrișor; Constantin, Nicolae Tiberiu; Mitrea, Ioan Liviu (Frontiers in Veterinary Science, 2024)
Male infertility is frequently caused by idiopathic or unexplained reasons, resulting in an increase in demand for assisted reproductive technologies. In buffaloes, more than in other animals due to reproductive hardiness, successful fertilisation needs spermatozoa to effectively transit the female reproductive system to reach the oocyte. This mechanism naturally picks high-quality sperm cells for conception, but when artificial reproductive technologies such as in vitro fertilisation, intracytoplasmic sperm injection, or intrauterine insemination are utilised, alternative techniques of sperm selection are necessary. Currently, technology allows for sperm sorting based on motility, maturity, the lack of apoptotic components, proper morphology, and even sex. This study provides current knowledge on all known techniques of sperm cell sorting in buffaloes, evaluates their efficiency, and discusses the benefits and drawbacks of each approach.